FAKTOR PENYEBAB KURANGNYAMINAT GENERASI MUDA PADA TRADISI BERZANJI DIDAIK KABUPATEN LINGGAPROVINSI KEPULAUANRIAU - Fatma Lingga Tari; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the lack of interest in the younger generation of the Berzanji tradition which will lead to drastic extinctions, lack of curiosity will cause various symptoms such as lack of knowledge of the Daik tradition. So the authors take the title of the research